2008
DOI: 10.1371/journal.pone.0002944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of bZIP Transcription Factors in Green Plant Evolution: Adaptive Features Emerging from Four Founder Genes

Abstract: BackgroundTranscription factors of the basic leucine zipper (bZIP) family control important processes in all eukaryotes. In plants, bZIPs are regulators of many central developmental and physiological processes including photomorphogenesis, leaf and seed formation, energy homeostasis, and abiotic and biotic stress responses. Here we performed a comprehensive phylogenetic analysis of bZIP genes from algae, mosses, ferns, gymnosperms and angiosperms.Methodology/Principal FindingsWe identified 13 groups of bZIP h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
294
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(318 citation statements)
references
References 119 publications
18
294
0
6
Order By: Relevance
“…Instead it looks like plants have evolved their own zinc responsive regulation system controlling sufficient uptake of zinc in case of deficiency, depending on bZIP19-or bZIP23-like genes. Putative orthologs have been found in monocots and dicots, but also in gymnosperms and lower plants like Physcomitrella patens (20). These genes can be distinguished from putative paralogues resembling the bZIP24 gene of Arabidopsis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead it looks like plants have evolved their own zinc responsive regulation system controlling sufficient uptake of zinc in case of deficiency, depending on bZIP19-or bZIP23-like genes. Putative orthologs have been found in monocots and dicots, but also in gymnosperms and lower plants like Physcomitrella patens (20). These genes can be distinguished from putative paralogues resembling the bZIP24 gene of Arabidopsis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…bZIP genes that are closely related to Arabidopsis bZIP19 and bZIP23 are found in several species, including rice, poplar, and soybean (respectively OsbZIP48, PtrbZIP38/PtrbZIP39, and GmbZIP121/GmbZIP122), but also in gymnosperms like Picea glauca and Pinus taeda (PgbZIP4 and PtbZIP12, respectively) and lower plants like the Bryophyte Physcomitrella patens (PpbZIP18 and PpbZIP19) (20) (Fig. S1 B and C).…”
Section: Zdre Is Present In the Promoter Of Arabidopsis Zinc-deficiency-mentioning
confidence: 99%
“…Applying a dynamic tree cut (Langfelder et al, 2008) to the clustering dendrogram, we identified 85 motif types ( Figure S2A). At the family level, motif clusters from the large and functionally diverse bZIP ( Figure 3A) and NAC families ( Figure S2B) closely reflected TF phylogeny (Corrêa et al, 2008;Olsen et al, 2005), indicating target sequences are conserved for close paralogs. Binding peaks of these TFs showed a range of enrichment in conserved non-coding regions (Haudry et al, 2013) (Figure S2C).…”
Section: The Arabidopsis Cistromementioning
confidence: 96%
“…They showed a total P value >10% from T000 to T048, perhaps reflecting the requirement for ethylene action in germination. bZIP proteins control seed and leaf development, nitrogen/carbon balance, and photomorphogenesis (33)(34)(35), whereas C3H proteins are implicated in embryogenesis (36) and stress response (37). The NAC gene family maintained high expression (P > 5%) until T030.…”
Section: Expression Dynamics Of Tf Gene Families During Germination Andmentioning
confidence: 99%